Mercury levels in the Smooth Hammerhead Shark Sphyrna zygaena (Carcharhiniformes: Sphyrnidae) from Northern Peru - Gonzalez-Pestana, Adriana (2017)
The smooth hammerhead shark Sphyrna zygaena (Linnaeus, 1758) is one of the elasmobranch species most used for human consumption in Peru. However, the level of mercury in hammerhead muscle tissue is unknown. This study assessed the level of mercury found in the muscle of hammerhead sharks and its relation with human health. Moreover, we evaluated the relationship between shark body size and mercury levels. We analyzed 27 muscle samples of neonates and juveniles captured in northern Peru. Mercury concentrations varied between 0.13 and 0.86 mg kg-1 wet weight. Moreover, we found a negative and significant relationship between shark body size and mercury levels. This study represents the first evaluation of mercury levels of sharks in Peru. Although the values found do not exceed levels recommended by the World Health Organization (< 1 mg kg-1), we recommend expanding this study to include other size classes of sharks as well as other marine resources used for human consumption.